Nannoliths content of MIRA-CP1 core, Portugal - Armand Hernández; Mario Cachao; Maria da Conceicao Freitas (PANGAEA, 2017)
Sixteen calcareous nannoplankton taxa and didemnid ascidian spicules were identified throughout MIRA-CP1 core (see Alday et al. 2006 for further details). On the basis of calcareous nannofossil (calcareous nannoplankton and ascidian spicules) assemblages, defined in terms of presence, species abundance, diversity and dominance, the MIRA-CP1 core (ca. 25 m thick) was spreviously divided into five different nannofossil zones 6 (NNZ). NNZ3 (16 m to 4.05 m) is characterized by high and persistent record on nannoliths. This zone can be further divided in two subzones: NNZ3A (16 m to 11.06 m), characterized by the relative dominance of Gephyrocapsa oceanica, Gephyrocapsa muellerae, Umbilicosphaera sibogae, Syracosphaera histrica-pulchra, Coronosphaera mediterranea and a dominance cycle of Coccolithus pelagicus braarudi and Calcidiscus leptoporus; and NNZ3B (11.06 m to 4.05 m), characterized by the relative dominance of Helicosphaera carteri, Braarudosphaera bigelowii together with ascidian spicules and a second dominance cycle of C. pelagicus braarudi and Calcidiscus leptoporus